In Vitro and In Vivo Antigen Presentation and Diagnosis Development of Recombinant Overlapping Peptides Corresponding to Mtb ESAT-6/CFP-10 - Zhang, Qing; Lu, Xiong; Gao, Liang; Tao, Siyu; Ge, Yinghua; Cui, Daocheng; Zhu, Renying; Lu, Wenshu; Wang, Jian; Jiang, Shisong (Frontiers in Immunology, 2022)
Cellular immunity in mycobacteria tuberculosis (Mtb) infection is important for both pathogenesis and final clearance of the intracellular Mtb infection. Moreover, it is valuable for the diagnosis of TB infection. In this pioneer work, we tested in vitro and in vivo antigen presentation and diagnostic application of a recombinant overlapping peptide protein which derived from two Mtb RD1 antigens ESAT-6 and CFP-10 (ROP-TB). The overlapping peptide sequence of ROP-TB is linked by Cathepsin S substrate and covers the whole length of the two proteins. ROP-TB can be expressed and purified from e.coli. Once taking in by antigen presenting cells, ROP-TB can be cleaved into a peptide pool by Cathepsin S inside the cells. We found, 1) in dendritic cells, ROP-TB can be processed in 6 hours of coculture, while the ESAT-6/CFP-10 fusion protein remains in the endosomal compartment. 2) In Mtb-infected mice, stronger specific T cell responses are stimulated by ROP-TB than pooled synthetic peptides derived from ESAT-6 and CFP-10. 3) For in vivo antigen presentation, in the model of guinea pigs infected with Mtb, ROP-TB elicits a delayed-type hypersensitivity (DTH) responses comparable to that of PPD and ESAT-6/CFP-10 fusion protein. 4) furthermore, in Mtb- infected cattle, ROP-TB elicits DTH responses. 5) In Mtb infected patients, ROP-TB stimulated cellular immune responses in all patients with different HLA phenotypes while a single peptide derived from the same proteins does not in all patients. In summary, the in vitro and in vivo data suggest that ROP-TB stimulates strong cellular immune response irrespective of HLA phenotypes and is therefore suitable for being used as in vitro and in vivo diagnosis.